Not so indifferent after all? Self-conscious atheism and the secularisation thesis - Bullivant, Stephen (Approaching Religion, 2012)
Commenting on the lack of self-conscious atheists in apparently secularised Western European societies, the British sociologist Steve Bruce has argued that strong expressions of unbelief are in fact symptomatic of religious cultures. In 1996’s Religion in the Modern World, for instance, he writes: ‘it should be no surprise that, though there are more avowed atheists than there were twenty years ago, they remain rare. Self-conscious atheism and agnosticism are features of religious cultures and [in Britain] were at their height in the Victorian era. They are postures adopted in a world where people are keenly interested in religion.’ (Bruce 1996: 58.) Likewise, discussing possible ‘endpoints’ of European secularisation in 2002’s God is Dead, Bruce states: In so far as I can imagine an endpoint, it would not be conscious irreligion; you have to care too much about religion to be irreligious. It would be widespread indifference (what Weber called being religiously unmusical); no socially significant shared religion; and religious ideas being no more common than would be the case if all minds were wiped blank and people began from scratch to think about the world and their place in it. (Bruce 2002: 42, my emphasis.)Paradoxical though it may sound at first, Bruce’s basic argument makes considerable sense. The idea that certain forms of particularly positive atheism – by which I mean a definite belief in the non-existence of a God or gods, as opposed to the simple absence of a belief in the same (negative atheism) – might be motivated, conditioned, or reinforced, by contrast with certain, socially prevalent religious beliefs or practices is scarcely controversial. After all, it would be strange to take one’s atheism seriously in a society where no one took theism seriously. A society that is indifferent to manifestations of religion (such as Bruce and others depict many late-modern western societies as being) ought, therefore, to be just as indifferent to manifestations of ‘nonreligion’.